Clinicopathologic Implications of Eukaryotic Initiation Factor 3f and Her‐2/neu Expression in Gastric Cancer. Issue 4 (14th February 2015) - Cheng, Yu; Zhou, Jin; Li, Honglun
Abstract Background: To detect the expression of eIF3f and human epidermal growth factor receptor 2 (Her‐2)/neu in gastric cancer (GC), correlation with their clinicopathological parameters and the relationship of eIF3f and Her‐2/neu in the occurrence and development of GC. Methods: A total of 195 gastrectomy specimens with stage I to III were examined for eIF3f expression by immunohistochemistry and for Her‐2/neu expression by fluorescence in situ hybridization (FISH) with the median follow‐up period of 38 months. Results: The positive expression rate of eIF3f in GC and adjacent noncancerous tissue were 33.8% and 59.5%, respectively. eIF3f levels were linked to more advanced tumor stages and likelihood of recurrence (all p < 0.05). The Kaplan–Meier survival curves indicated that decreased expression of eIF3f could serve as a prognosis marker for poor outcome of GC patients (p = 0.04). 15.9% of GC specimens were positive for Her‐2/neu, but whose expression was of no correlation with patients' survival. Patients who were positive for Her‐2/neu also had high eIF3f expression levels (p = 0.0295). Conclusion: Results suggest that eIF3f may play an important role in recurrence, thus representing a promising predictive marker for the prognosis of GC. But Her‐2/neu has no relationship with the prognosis of GC. The clinical significance of eIF3f and Her‐2/neu remains to be further investigated.